Study on Online Game Addiction Among Students of State Senior High School 6 Padangsidimpuan City - Mandasari Dalimunthe, Efrida (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
The rapid development of knowledge and technology lately has increasingly had a major impact on people's lives. The location of the study was at SMA Negeri 6 Padangsidimpuan City. The population used in this study were all students of SMA Negeri 6 Padangsidimpuan City. Online Game Addiction is categorized in the very high category as many as 49 students with a percentage of 47.57%. Then, 6 students are in the high category with a percentage of 5.83%, 7 students are in the medium category with a percentage of 6.80%. In addition, there are 25 students in the low category with a percentage of 24.27%, and there are 16 students in the very low category with a percentage of 15.53%. The aspects of online game addiction used are; the average score of importance obtained is 16.38 with a percentage of 65.52%. The tolerance aspect is 16.43 or equivalent to 65.72%, the mood modification aspect is at an average of 15.94 or equivalent to 63.76%. In addition, the average score on the repetition or relapse aspect is 16.02 or equivalent to 64.08%, the average score on the withdrawal aspect is 16.82 or equivalent to 67.28%, and the average score on the conflict aspect is 15.91 or equivalent to 63.64%. Finally, the average score on the problem aspect is 16.53 or equivalent to 66.12%.